PERITEXTUAL HYBRIDITY ELEMENTS IN TRANSLATIONS OF THE “BALTAGUL” NOVEL BY MIHAIL SADOVEANU - GENCĂRĂU, Ștefan; ADAM, Ema Ileana (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Peritextual Hybridity Elements in Translations of the Baltagul Novel by Mihail Sadoveanu. Within this stage of our research, we focus our attention on several of the elements rarely taken into consideration while debating translation analysis, in our case, the translations of Baltagul novel [The Hatchet] into French and English. We subscribe to the method proposed by Danielle Risterucci-Roudnicky because it offers the analyst the parameters of a complex approach to the translated work. The distinction the method proposes concentrates the analyst’s attention upon the translator’s footprints as well as on the elements outside the text itself, but strictly connected to it, insuring its position within the cultural space into which it is inserted, facilitating its selection for reading and implicitly, its decoding. Consequently, the translated work bears the marks of a hybridity with benefic, even protective effects. Peritextually, hybridity has its sources in the references to the printing house, support, collection, illustration, cover, in metatexts as the title, preface, afterword, and the footnotes, as well as in the history of the external interest for such a work. Although we mention that textual hybridity diversifies with respect to the register in which the resistance of the original is felt within the translated work, advancing, in agreement with the accepted model, a typology which includes the auctorial hybridity, referential hybridity, and poetic hybridity, we approach, in the limits of the present article, only a few of the peritextual hybridity elements especially because the three versions of the Baltagul novel, two of which in French, chronologically due to Al. Duiliu Zamfirescu and Profira Sadoveanu and one in English owed to Eugenia Farca, should be discussed within the larger context implying the totality of the factors capable of contributing to the reception and thus to the circulation of the translated text. Rezumat. Elemente de hibriditate peritextuală în traducerea romanului Baltagul de Mihail Sadoveanu. Ne îndreptăm în această etapă a cercetării noastre atenţia asupra unora dintre elementele rar luate în discuţie în analiza traducerii, în cazul nostru: a romanului Baltagul, în franceză şi în engleză. Subscriem unei metode propuse de Danielle Risterucci-Roudnicky, pentru că aceasta oferă analistului parametrii abordării complexe a operei în traducere. Distincţia pe care metoda o propune centrează atenţia analistului asupra urmelor traducătorului, precum şi a elementelor din afara textului propriu-zis, dar în legătură strictă cu acesta, care îi asigură poziţia în spaţiul cultural în care se inserează, îi facilitează selecţia spre lectură şi, implicit, decodarea. Opera tradusă poartă în consecinţă însemnele unei hibridităţi cu efecte benefice, chiar protectoare. Peritextual, hibriditatea îşi are sursele în referinţele la editură, suport, colecție, ilustrație, copertă, în metatexte ca titlul, prefața, postfața și notele de subsol, precum şi în istoria interesului extern pentru o astfel de operă. Deşi amintim că hibriditatea textuală se diversifică în funcţie de registrul în care se resimte rezistenţa originalului în opera tradusă, avansând, în acord cu modelul acceptat, o tipologie ce include hibriditatea auctorială, hibriditatea referenţială şi hibriditatea poetică, abordăm în limitele acestui articol doar unele dintre elementele de hibriditate peritextuală tocmai pentru că cele trei versiuni ale romanului Baltagul, dintre care două în franceză datorate în ordine lui Al. Duiliu Zamfirescu şi Profirei Sadoveanu şi una în engleză datorată Eugeniei Farca, trebuie puse în discuţie în contextul mai larg ce implică ansamblul factorilor în măsură să asigure receptarea şi astfel circulaţia textului tradus. Cuvinte cheie: Sadoveanu, Baltagul, hibriditate peritextuală, metatext, titlu.